Immunobiotics—interactions of beneficial microbes with the immune system - Villena, Julio Cesar (2017)
The term ?immunobiotics? has been proposed to define microbial strains able to beneficially regulate the mucosal immune system. Research in immunobiotics has significantly evolved as researchers employed cutting-edge technologies to investigate the complex interactions of these beneficial microorganisms with the immune system. During the last decade, our understanding of immunobiotics-host interaction was profoundly transformed by the discovery of microbial molecules and host receptors involved in the modulation of gut associated immune system, as well as the systemic and distant mucosal immune systems.